America : its people and values - Wood, Leonard, 1923-; Gabriel, Ralph Henry, 1890-1987 (New York : Harcourt Brace Jovanovich, 1971)
A history text emphasizing the building of the American system and the goals and policies of a democracy.
Includes bibliographical references.
Keywords: United States -- History -- Juvenile literature; United States -- History